Physiologically Based Models in Regulatory Submissions: Output From the ABPI/MHRA Forum on Physiologically Based Modeling and Simulation. (2nd April 2015) - Shepard, T; Scott, G; Cole, S; Nordmark, A; Bouzom, F
<x xml:space="preserve">Abstract</x> Under the remit of the Ministerial Industry Strategy Group (MISG), the Association of the British Pharmaceutical Industry (ABPI) and Medicines and Healthcare products Regulatory Agency (MHRA) hosted a meeting to explore physiologically based pharmacokinetic modeling and simulation, focusing on the clinical component of regulatory applications. The meeting took place on 30 June 2014 with international representatives from industry, academia, and regulatory agencies. Discussion topics were selected to be complementary to those discussed at an earlier US Food and Drug Administration (FDA) meeting. This report summarizes the meeting outcomes, focusing on the European regulatory perspective.